Optimalisasi Administrasi Tenaga Pendidik dan Tenaga Kependidikan di Era Society 5.0 - Nur ‘Azizah Yunara Putri; Puti Jona Wildan; Ahmad Sabri; Rully Hidayatullah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Educators are at the forefront of educating the nation through various methods, paths, and levels of teaching. Students are working adults who enter the world of education (school) and return to society. Providing this foundation throughout life is the task of teachers, the backbone of the school. Management can be viewed as a process or as a task. Management as a process is the same as management in a broad sense. Management as a process of activities includes planning, organizing, directing or directing, and monitoring or controlling. These four components form a system that is interested and integrated as a whole. This means that your plan needs to be organized, managed, and monitored. The organization also needs to be planned, managed, and controlled. Control also needs to be planned, organized and controlled. Therefore, school management is the activity of allocating, organizing and using all resources to achieve educational goals in schools effectively and efficiently.